Trivariate Modelling of the Nexus Between Financial Development, Globalization and Economic Growth: Insight from African Countries - Ahmed, Azeez Olarewaju (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
Financial development has been identified as main drivers of economic growth. However, empirical probe of this nexus remains inconclusiveness due use of an inappropriate proxy by previous studies, and the inability of previous studies to consider globalization in this nexus. To this end, we probe the finance-growth nexus in the presence of globalization by applying the Pooled Mean Group (PMG) estimator to a sample of 21 countries spanning 1990–2017. The empirical results affirm the supply-leading hypothesis which indicates that financial development spur economic growth. In addition, our estimate provides evidence of a positive linear relationship between globalization and economic growth. Further, results indicate that physical capital investment plays an important role in accelerating economic performance of African economies. Based on these findings, it is important for African countries to promote globalization-financial development policies in order to have access to alternative sources of external financing and attract foreign investment that can spur growth of African countries.